World War I in South Africa's Memory - (:unkn) unknown (My University, 2014)
Historical memory of the Great War in South Africa has long been characterised by political divisions and contestations, as well as by a steadily decreasing presence in public consciousness and in acts of war remembrance, especially in more recent decades. This article explores the complex place of Great War experience in South Africa’s modern history, and evaluates the significance of its shifting meanings. It also considers how the political agenda of post-apartheid society may be reengaging with world war commemoration on a new black nationalist basis.
Keywords: African Research